Valtorno-Mourão Dam. Reinforcement of the foundation grout due to problems detected during the first filling - Marcelino, J. (2012)
The Valtorno-Mourão dam in the municipality of Vila Flor is intended to create a reservoir with the total volume of 1.12 x106 m3 for water supply. The embankment has a crest length of 150 m and 32 m of maximum height. It as a homogeneous profile including a sub-vertical filter. The construction of the dam took place between July 2004 and January 2006. During the first filling, the comparison of the results of monitoring with the predictions from the Monitoring Plan lead to the conclusion that the dam was not having the expected behaviour, both for the amount of flow, which was roughly ten times higher than it was expected, and for the pore pressures measured in some piezometers. The Tras-os-Montes region in Portugal has normally severe conditions of water supply and the amount of loss in the dam was not compatible with normal supply to the populations. Given this scenario, it was decided to stop the first filling of the reservoir to allow the diagnosis of deficiencies. As a result, a new grouting treatment of the foundation was made, so that currently, the dam exhibits the desired behaviour. This paper seeks to describe the fundamental characteristics of the dam and foundation, some aspects of the construction, the diagnosis of disabilities, the treatment performed and, finally, the behaviour observed up to the date.